High-temperature-resistant wrought aluminum alloy and preparation method thereof

The introduction of titanium powder and a modified epoxy resin coating in the high-temperature forming process addresses the inefficiencies and corrosion issues in existing aluminum alloy forming methods, enhancing mechanical strength and corrosion resistance.

CN119710328APending Publication Date: 2025-03-28NANJING ZHANDA NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411591184.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Current aluminum alloy forming methods, particularly through mechanical processing, are costly and inefficient, and the corrosion susceptibility of aluminum alloys limits their applications due to the fragility of epoxy coatings which lead to premature failure.

Method used

A high-temperature forming aluminum alloy is developed by adding a small amount of titanium powder, followed by water quenching, pre-forming, and applying a modified epoxy resin coating that combines silane and molybdenum vanadate compounds to enhance mechanical strength and corrosion resistance.

Benefits of technology

The process significantly improves the mechanical strength, corrosion resistance, and formability of the alloy by creating a dense crystal structure and strong adhesion of the coating, reducing corrosion and increasing the lifespan of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005125629240000071
    Figure BDA0005125629240000071
Patent Text Reader

Abstract

The invention discloses a high-temperature-resistant wrought aluminum alloy and a preparation method thereof, and relates to the technical field of aluminum alloys. Aluminum alloy serves as a metal raw material, a small amount of titanium element is added, and the mechanical strength of the alloy is enhanced; after heat preservation is conducted for a period of time under the over-high-temperature condition, the overall mechanical strength, tensile strength and ductility of the alloy are enhanced; secondly, pre-deformation, water quenching and aging treatment are conducted, and the strength and plasticity of the alloy are further enhanced; and finally, the alloy surface is subjected to sand blasting and coated with a modified epoxy resin coating, so that the effects of high strength and corrosion resistance are achieved. According to the modified epoxy resin coating, carboxyl ethyl silanetriol sodium salt and epoxy resin are subjected to esterification combination, the hardness of the coating after curing on the surface of the aluminum alloy is improved, and meanwhile the adhesive ability and the corrosion resistance between the coating and the aluminum alloy are enhanced; and then mixing with sodium vanadium molybdate, and uniformly coating on the surface of the aluminum alloy to relieve metal corrosion and improve the adhesion strength between the coating and the alloy interface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum alloys, and in particular to a high-temperature resistant deformation aluminum alloy and a preparation method thereof. Background Art

[0002] The main forming methods of aluminum alloys are plastic processing and solidification processing. The plastic processing method uses the good plasticity of aluminum alloys to apply a certain form of external force under certain conditions such as temperature and forming speed to overcome the deformation resistance of the metal and cause it to undergo plastic deformation, thereby obtaining a product with a certain shape, specification, size and organizational properties. The plastic processing method mainly corresponds to deformed aluminum alloys, and the main methods include rolling, extrusion, drawing, forging, stamping, etc. At present, deformed aluminum alloys are mainly processed by forging technology, which has high processing costs and low efficiency, and serious waste of resources due to excessive mechanical processing. Based on the dual needs of modern industry for near-net-shape forming and high mechanical performance products, there is an urgent need for a new processing technology that can simultaneously give full play to the performance advantages of the alloy and the advantages of forming efficiency.

[0003] Aluminum alloys have the advantages of light weight and high specific strength, and are widely used in the automotive, aerospace, marine and other fields. However, due to the low corrosion potential of aluminum alloys themselves, they are prone to corrosion, which limits many potential applications of aluminum alloys. In order to control the corrosion problem of aluminum alloys, epoxy coating is an effective protective measure. However, due to the inherent brittleness of epoxy resins themselves, after the solvent evaporates, micropores will inevitably be generated and channels will be formed. Corrosive electrolytes can easily penetrate through the micropores and channels, resulting in the formation and accumulation of corrosion products under the coating, causing the coating to lose adhesion and delamination. Therefore, pure epoxy organic coatings need to be modified to improve their service life and range. Summary of the invention

[0004] The object of the present invention is to provide a high temperature resistant deformation aluminum alloy and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a high temperature resistant deformation aluminum alloy, which is made of aluminum alloy as raw material, a small amount of titanium powder is added, and the alloy is immediately quenched in water after being melted at an excessively high temperature, and then pre-deformed and aged, and then a modified epoxy resin coating is coated on the surface to obtain the alloy.

[0006] Furthermore, the modified epoxy resin coating is prepared by combining carboxyethylsilanetriol sodium salt with epoxy resin by esterification and then mixing with sodium molybdate vanadate.

[0007] Furthermore, a method for preparing a high temperature resistant deformation aluminum alloy comprises the following preparation steps:

[0008] (1) Under a nitrogen atmosphere, 20 to 30 parts of epoxy resin are dissolved in 100 to 150 parts of toluene, and after stirring evenly, 28 to 40 parts of carboxyethylsilanetriol ethanol solution are added, the temperature is raised to 80 to 90° C., 1 to 3 parts of 8 wt% dibutyltin dilaurate toluene solution are added dropwise, the temperature is continued to be raised to 95 to 105° C., and the mixture is reacted for 4 to 8 hours under stirring at 120 rpm, concentrated for 2 to 4 hours at a vacuum degree of -0.08 MPa and 40° C., 54 to 82 parts of ethanol, 4 to 8 parts of sodium molybdate vanadate, and 13 to 21 parts of 650 polyamide resin curing agent are added and mixed evenly to obtain a modified epoxy resin coating material;

[0009] (2) placing 58 to 96 parts of aluminum alloy and 0.2 to 0.4 parts of titanium powder in a furnace, melting at 740 to 780° C. for 40 to 50 minutes, and then casting, wherein the casting temperature is 680 to 720° C., the casting speed is 55 to 75 mm / min, the casting cooling water temperature is 18 to 24° C., and the casting cooling water pressure is 0.05 to 0.85 MPa, placing on a hot rolling mill at 300 to 400° C. to a thickness of 2 to 3 mm, immersing in a water pool at 20 to 30° C. for 5 to 15 seconds, and then standing at 170 to 190° C. for 4 to 12 hours and at 20 to 25° C. for 18 to 36 hours to obtain an aluminum alloy blank;

[0010] (3) The surface of the aluminum alloy blank is sandblasted, and a modified epoxy resin coating material is applied to the surface of the aluminum alloy blank with a coater, and cured at 60 to 70° C. for 8 to 12 hours to obtain a high temperature resistant deformation aluminum alloy.

[0011] Furthermore, the epoxy resin model in step (1) is any one of EPM-420, MF-3285, and 3101G.

[0012] Furthermore, the preparation steps of the carboxyethylsilanetriol ethanol solution in step (1) are as follows: dissolving 3 to 5 parts of carboxyethylsilanetriol sodium salt in 24 to 40 parts of ethanol, stirring evenly, adding hydrochloric acid ethanol solution to adjust the pH, filtering the filtrate, and obtaining the carboxyethylsilanetriol ethanol solution.

[0013] Furthermore, the concentration of hydrochloric acid in the hydrochloric acid-ethanol solution is 1 mol / L; and the pH value of the solution after pH adjustment is 4-6.

[0014] Furthermore, the preparation method of the sodium molybdate in step (1) is as follows: 15 to 25 parts of sodium molybdate, 18 to 30 parts of sodium orthovanadate, and 132 to 220 parts of water are mixed evenly, transferred into an autoclave, reacted at 200 to 240° C. for 12 to 24 hours, naturally cooled to room temperature, filtered to obtain a solid, washed alternately with deionized water and ethanol for 3 times, dried in an oven at 50 to 60° C. for 10 to 16 hours, and crushed into powder to obtain sodium molybdate.

[0015] Furthermore, the aluminum alloy model in step (2) is any one of 6061, 6063, and 7075.

[0016] Furthermore, the diameter of the rolling rollers in the hot rolling mill in step (2) is 300 to 400 mm.

[0017] Furthermore, the thickness of the coating in step (3) is 100 to 120 μm.

[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0019] The present invention uses aluminum alloy as a metal raw material, adds a small amount of titanium element, reduces the solid solution content of manganese element in the cast lead alloy matrix, eliminates the coarse block phase distributed in the original crystal and forms a spherical phase, significantly reduces the strip and broken block compounds at the grain boundary, thereby enhancing the mechanical strength of the alloy; then, the alloy is kept warm for a period of time under an over-high temperature condition, and the over-high temperature heating is performed to make the precipitation phase inside the alloy quickly form a liquid phase at the grain boundary, rather than being dissolved into the interior of the Al matrix in large quantities, and the insoluble dispersed particles are wetted and dissolved by the liquid phase between the grains, thereby promoting metal recrystallization and reducing the coalescence growth trend between the grains, thereby enhancing the overall mechanical strength of the alloy; secondly, a pre-deformation treatment is performed to provide more effective shape for the precipitation phase The nucleus position increases the number of precipitated phase nuclei, improves the dislocation density, and achieves the effect of improving the strength of the material; then water quenching treatment can make it cool quickly to room temperature. The huge temperature difference makes the crystals inside the alloy arranged in order, forming more subgrain boundaries and fine grains and high-density grain boundaries, which can increase the toughness and plasticity of the aluminum alloy, thereby improving its tensile strength and ductility. Then aging treatment is carried out, and the fine precipitated phases are continuously distributed on the grain boundaries, and the grain boundary non-precipitation precipitation zone is narrow, the stress concentration is small, and it is not easy to fracture along the grain, thereby enhancing the plasticity of the alloy; finally, the alloy surface is sandblasted and coated with a modified epoxy resin coating to achieve high strength and corrosion resistance.

[0020] Among them, the modified epoxy resin coating utilizes the esterification of the carboxyl group in the sodium salt of carboxyethylsilanetriol with the hydroxyl group in the side chain of the epoxy resin to reduce the distance between the epoxy resin molecular chains, thereby increasing the intermolecular force, and then improving the hardness of the coating after curing on the surface of the aluminum alloy. At the same time, it can be combined with the Si-O-Al chemical bond on the surface of the aluminum alloy to enhance the adhesion and corrosion resistance between the coating and the aluminum alloy; it is then mixed with sodium vanadium molybdate and evenly coated on the surface of the aluminum alloy to better fill the cracks in the epoxy resin coating, forming a certain maze effect, reducing the diffusion path of the corrosive medium, and alleviating the corrosion of the metal. In addition, there are more concave and convex interfaces on the alloy surface treated by sandblasting, which can more effectively interact with the epoxy coating. On this basis, the special structure of sodium molybdate is utilized to form a stable bridge to improve the adhesion strength of the coating and the alloy interface. DETAILED DESCRIPTION

[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the high temperature resistant deformation aluminum alloy prepared in the following examples are as follows:

[0023] Tensile strength: Take the embodiment and comparative example of the same size and test them according to GB / T 228.1.

[0024] Stress corrosion index: Take the embodiment and comparative example of the same size and test them according to GB / T 15970.7.

[0025] Example 1

[0026] (1) dissolving 3 parts of carboxyethylsilanetriol sodium salt in 24 parts of ethanol, stirring evenly, adding a hydrochloric acid-ethanol solution having a hydrochloric acid concentration of 1 mol / L to adjust the pH to 4, filtering the filtrate to obtain a carboxyethylsilanetriol ethanol solution;

[0027] (2) 15 parts of sodium molybdate, 18 parts of sodium orthovanadate and 132 parts of water were mixed evenly, transferred into an autoclave, reacted at 200° C. for 12 hours, cooled naturally to room temperature, filtered to obtain a solid, washed alternately with deionized water and ethanol three times, dried in an oven at 50° C. for 10 hours, and crushed into powder to obtain sodium molybdate;

[0028] (3) Under a nitrogen atmosphere, 20 parts of EPM-420 epoxy resin were dissolved in 100 parts of toluene, and after stirring, 28 parts of carboxyethylsilanetriol ethanol solution were added, the temperature was raised to 80° C., 1 part of 8 wt% dibutyltin dilaurate toluene solution was added dropwise, and the temperature was continued to rise to 95° C., and the mixture was reacted for 4 h under stirring at 120 rpm, and concentrated for 2 h at a vacuum degree of -0.08 MPa and 40° C., and 54 parts of ethanol, 4 parts of sodium molybdate vanadate, and 13 parts of 650 polyamide resin curing agent were added and mixed evenly to obtain a modified epoxy resin coating material;

[0029] (4) 58 parts of 6061 aluminum alloy and 0.2 parts of titanium powder were placed in a furnace, melted at 740° C. for 40 min, and then cast at a casting temperature of 680° C., a casting speed of 55 mm / min, a casting cooling water temperature of 18° C., and a casting cooling water pressure of 0.05 MPa. The aluminum alloy billet was hot rolled at 300° C. to a thickness of 2 mm on a hot rolling mill with a roller diameter of 300 mm, immersed in a 20° C. water pool for 5 s, and then kept at 170° C. for 4 h and at 20° C. for 18 h to obtain an aluminum alloy billet;

[0030] (5) The surface of the aluminum alloy blank was sandblasted, and a 100 μm thick modified epoxy resin coating material was applied on the surface of the aluminum alloy blank with a coater, and cured at 60° C. for 8 h to obtain a high temperature resistant deformation aluminum alloy.

[0031] Example 2

[0032] (1) dissolving 4 parts of carboxyethylsilanetriol sodium salt in 32 parts of ethanol, stirring evenly, adding a hydrochloric acid-ethanol solution having a hydrochloric acid concentration of 1 mol / L to adjust the pH to 5, filtering the filtrate to obtain a carboxyethylsilanetriol ethanol solution;

[0033] (2) 20 parts of sodium molybdate, 24 parts of sodium orthovanadate and 176 parts of water were mixed evenly, transferred into an autoclave, reacted at 220° C. for 18 hours, cooled naturally to room temperature, filtered to obtain a solid, washed alternately with deionized water and ethanol three times, dried in an oven at 55° C. for 13 hours, and crushed into powder to obtain sodium molybdate;

[0034] (3) Under a nitrogen atmosphere, 25 parts of MF-3285 epoxy resin were dissolved in 125 parts of toluene, and 34 parts of carboxyethylsilanetriol ethanol solution were added after stirring evenly, and the temperature was raised to 85° C., and 2 parts of 8wt% dibutyltin dilaurate toluene solution were added dropwise, and the temperature was continued to rise to 100° C., and the mixture was reacted for 6 hours under stirring at 120 rpm, and concentrated for 3 hours at a vacuum degree of -0.08 MPa and 40° C., and 68 parts of ethanol, 6 parts of sodium molybdate vanadate, and 17 parts of 650 polyamide resin curing agent were added and mixed evenly to obtain a modified epoxy resin coating material;

[0035] (4) 77 parts of 6063 aluminum alloy and 0.3 parts of titanium powder were placed in a furnace, melted at 760° C. for 45 min, and then cast at a casting temperature of 700° C., a casting speed of 65 mm / min, a casting cooling water temperature of 21° C., and a casting cooling water pressure of 0.45 MPa. The aluminum alloy was placed on a hot rolling mill with a roller diameter of 350 mm and hot rolled at 350° C. to a thickness of 2.5 mm. The aluminum alloy was immersed in a water pool at 25° C. for 10 s, and then kept at 180° C. for 8 h and at 22.5° C. for 24 h to obtain an aluminum alloy blank.

[0036] (5) The surface of the aluminum alloy blank was sandblasted, and a modified epoxy resin coating material with a thickness of 110 μm was applied to the surface of the aluminum alloy blank with a coater, and then cured at 65° C. for 10 h to obtain a high temperature resistant deformation aluminum alloy.

[0037] Example 3

[0038] (1) dissolving 5 parts of carboxyethylsilanetriol sodium salt in 40 parts of ethanol, stirring evenly, adding a hydrochloric acid-ethanol solution having a hydrochloric acid concentration of 1 mol / L to adjust the pH to 6, filtering the filtrate to obtain a carboxyethylsilanetriol ethanol solution;

[0039] (2) 25 parts of sodium molybdate, 30 parts of sodium orthovanadate, and 220 parts of water were mixed evenly, transferred into an autoclave, reacted at 240° C. for 24 hours, cooled naturally to room temperature, filtered to obtain a solid, washed alternately with deionized water and ethanol three times, dried in an oven at 60° C. for 16 hours, and crushed into powder to obtain sodium molybdate;

[0040] (3) Under a nitrogen atmosphere, 30 parts of 3101G epoxy resin were dissolved in 150 parts of toluene, and after stirring, 40 parts of carboxyethylsilanetriol ethanol solution were added, the temperature was raised to 90° C., 3 parts of 8 wt% dibutyltin dilaurate toluene solution were added dropwise, the temperature was continued to be raised to 105° C., and the mixture was reacted for 8 h under stirring at 120 rpm, and concentrated for 4 h at a vacuum degree of -0.08 MPa and 40° C., 82 parts of ethanol, 8 parts of sodium molybdate vanadate, and 21 parts of 650 polyamide resin curing agent were added and mixed evenly to obtain a modified epoxy resin coating material;

[0041] (4) 96 parts of 7075 aluminum alloy and 0.4 parts of titanium powder were placed in a furnace, melted at 780° C. for 50 min, and then cast, wherein the casting temperature was 720° C., the casting speed was 75 mm / min, the casting cooling water temperature was 24° C., and the casting cooling water pressure was 0.85 MPa. The aluminum alloy billet was hot rolled at 400° C. to a thickness of 3 mm on a hot rolling mill with a roller diameter of 400 mm, immersed in a 30° C. water pool for 15 s, and then kept at 190° C. for 12 h and at 25° C. for 36 h to obtain an aluminum alloy billet;

[0042] (5) The surface of the aluminum alloy blank was sandblasted, and a 120 μm thick modified epoxy resin coating material was applied on the surface of the aluminum alloy blank with a coater, and the coating was cured at 70° C. for 12 h to obtain a high temperature resistant deformation aluminum alloy.

[0043] Comparative Example 1

[0044] The difference between Comparative Example 1 and Example 2 is that step (4) is different. Step (4) is changed to: 77 parts of 6063 aluminum alloy are placed in a furnace, melted at 760°C for 45 minutes, and then cast at a casting temperature of 700°C, a casting speed of 65 mm / min, a casting cooling water temperature of 21°C, and a casting cooling water pressure of 0.45 MPa. The aluminum alloy billet is hot-rolled at 350°C on a hot rolling mill with a roll diameter of 350 mm to a thickness of 2.5 mm, immersed in a water pool at 25°C for 10 seconds, and then kept at 180°C for 8 hours and 22.5°C for 24 hours to obtain an aluminum alloy billet. The remaining steps are the same as those in Example 2.

[0045] Comparative Example 2

[0046] The difference between Comparative Example 2 and Example 2 is that step (4) is different. Step (4) is changed to: 77 parts of 6063 aluminum alloy and 0.3 parts of titanium powder are placed in a furnace, semi-melted at 550°C for 45 minutes, and then cast, wherein the casting temperature is 700°C, the casting speed is 65mm / min, the casting cooling water temperature is 21°C, and the casting cooling water pressure is 0.45MPa, and the aluminum alloy blank is obtained by hot rolling at 350°C on a hot rolling mill with a roller diameter of 350mm to a thickness of 2.5mm, immersing it in a water pool at 25°C for 10s, and then standing at 180°C for 8h and 22.5°C for 24h. The remaining steps are the same as those in Example 2.

[0047] Comparative Example 3

[0048] The difference between Comparative Example 3 and Example 2 is that step (4) is different. Step (4) is changed to: 77 parts of 6063 aluminum alloy and 0.3 parts of titanium powder are placed in a furnace, melted at 760°C for 45 minutes, and then cast, wherein the casting temperature is 700°C, the casting speed is 65mm / min, the casting cooling water temperature is 21°C, and the casting cooling water pressure is 0.45MPa, and the aluminum alloy blank is obtained by hot rolling at 350°C on a hot rolling mill with a roller diameter of 350mm to a thickness of 2.5mm, and then standing at 180°C for 8h and 22.5°C for 24h. The remaining steps are the same as those in Example 2.

[0049] Comparative Example 4

[0050] The difference between Comparative Example 4 and Example 2 is that step (4) is different. Step (4) is changed to: 77 parts of 6063 aluminum alloy and 0.3 parts of titanium powder are placed in a furnace, melted at 760°C for 45 minutes, and then cast, wherein the casting temperature is 700°C, the casting speed is 65mm / min, the casting cooling water temperature is 21°C, and the casting cooling water pressure is 0.45MPa, and then the aluminum alloy blank is kept at 180°C for 8 hours, kept at 22.5°C for 24 hours, and immersed in a 25°C water pool for 10 seconds to obtain the aluminum alloy blank. The remaining steps are the same as those in Example 2.

[0051] Comparative Example 5

[0052] The difference between Comparative Example 5 and Example 2 is that step (4) is different. Step (4) is changed to: 77 parts of 6063 aluminum alloy and 0.3 parts of titanium powder are placed in a furnace, melted at 760°C for 45 minutes, and then cast, wherein the casting temperature is 700°C, the casting speed is 65mm / min, the casting cooling water temperature is 21°C, and the casting cooling water pressure is 0.45MPa. The aluminum alloy blank is placed on a hot rolling mill with a roller diameter of 350mm and hot rolled at 350°C to a thickness of 2.5mm, immersed in a water pool of 25°C for 10s, and naturally cooled to 22.5°C to obtain an aluminum alloy blank. The remaining steps are the same as those in Example 2.

[0053] Comparative Example 6

[0054] The difference between Comparative Example 6 and Example 2 is that step (1) is omitted, and step (3) is changed to: 25 parts of MF-3285 epoxy resin, 68 parts of ethanol, 6 parts of sodium molybdate vanadate, and 17 parts of 650 polyamide resin curing agent are mixed uniformly to prepare a modified epoxy resin coating material. The remaining steps are the same as those of Example 2.

[0055] Comparative Example 7

[0056] The difference between Comparative Example 7 and Example 2 is that there is no step (2), and step (3) is changed to: Under a nitrogen atmosphere, 25 parts of MF-3285 epoxy resin are dissolved in 125 parts of toluene, and 34 parts of carboxyethylsilanetriol ethanol solution are added after stirring evenly, and the temperature is raised to 85° C., 2 parts of 8wt% dibutyltin dilaurate toluene solution are added dropwise, and the temperature is continued to be raised to 100° C., and the mixture is reacted for 6 hours under stirring at 120 rpm, and concentrated for 3 hours at a vacuum degree of -0.08 MPa and 40° C., and 68 parts of ethanol and 17 parts of 650 polyamide resin curing agent are added and mixed evenly to obtain a modified epoxy resin coating material. The remaining steps are the same as those of Example 2.

[0057] Effect example

[0058] Table 1 below shows the performance analysis results of high temperature resistant deformation aluminum alloys using Examples 1 to 3 of the present invention and Comparative Examples 1 to 7.

[0059] Table 1

[0060]

[0061] From the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 1, it can be found that adding a small amount of titanium element reduces the solid solution content of manganese element in the cast lead alloy matrix, eliminates the coarse block phase distributed in the original crystal and forms a spherical phase, significantly reduces the strip and block compounds at the grain boundary, and enhances the mechanical strength of the alloy; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 2, it can be found that keeping the temperature under excessively high temperature for a period of time can make the precipitation phase inside the alloy quickly form a liquid phase at the grain boundary, instead of dissolving into the Al matrix in large quantities, and the insoluble dispersed particles are wetted and dissolved by the liquid phase between the grains, which promotes metal recrystallization and reduces the grain size. The coalescence growth trend between the alloys is enhanced, thereby enhancing the overall mechanical strength of the alloy; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 3, it can be found that water quenching treatment is immediately performed after high-temperature insulation, so that the alloy can be quickly cooled to room temperature. The huge temperature difference makes the crystals inside the alloy arranged in order, forming more subgrain boundaries, fine grains, and high-density grain boundaries, which can increase the toughness and plasticity of the aluminum alloy, and improve its tensile strength and ductility; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 4, it can be found that pre-deformation treatment of the alloy provides more effective nucleation sites for the precipitated phase, increases the number of precipitated phase nuclei, increases the dislocation density, and achieves the improvement of The effect of improving the strength of the material; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 5, it can be found that after aging treatment, fine precipitated phases are continuously distributed on the grain boundaries, and the grain boundary non-precipitated precipitation zone is narrow, the stress concentration is small, and it is not easy to break along the crystal, thereby enhancing the plasticity of the alloy; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 6, it can be found that the carboxyl group in the sodium salt of carboxyethylsilanetriol is esterified with the hydroxyl group in the side chain of the epoxy resin to reduce the distance between the molecular chains of the epoxy resin, thereby increasing the intermolecular force, thereby improving the hardness of the coating after curing on the surface of the aluminum alloy, and at the same time being able to The alloy surface is combined with Si-O-Al chemical bonds to enhance the adhesion and corrosion resistance between the coating and the aluminum alloy. From the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 6, it can be found that when mixed with sodium vanadium molybdate and evenly coated on the surface of the aluminum alloy, the cracks in the epoxy resin coating can be better filled, a certain maze effect can be formed, the diffusion path of the corrosive medium can be reduced, and the corrosion of the metal can be alleviated. In addition, there are more concave and convex interfaces on the alloy surface treated by sandblasting, which can more effectively interact with the epoxy coating. On this basis, the special structure of sodium molybdate is used to form a stable bridge to improve the adhesion strength of the coating and the alloy interface.

[0062] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A high temperature resistant deformation aluminum alloy, characterized in that: The high temperature deformation resistant aluminum alloy is prepared by using aluminum alloy as raw material, adding a small amount of titanium powder, immediately quenching with water after being melted at an excessively high temperature, and then pre-deforming and aging treatment, and then coating a modified epoxy resin coating on the surface.

2. The high temperature resistant deformation aluminum alloy according to claim 1, characterized in that: The modified epoxy resin coating is prepared by combining carboxylethylsilanetriol sodium salt with epoxy resin through esterification and then mixing with sodium molybdate vanadate.

3. A method for preparing a high temperature resistant deformable aluminum alloy, characterized in that: The method comprises the following preparation steps: (1) Under a nitrogen atmosphere, 20 to 30 parts of epoxy resin are dissolved in 100 to 150 parts of toluene, and after stirring evenly, 28 to 40 parts of carboxyethylsilanetriol ethanol solution are added, the temperature is raised to 80 to 90° C., 1 to 3 parts of 8 wt% dibutyltin dilaurate toluene solution are added dropwise, the temperature is continued to be raised to 95 to 105° C., and the mixture is reacted for 4 to 8 hours under stirring at 120 rpm, concentrated for 2 to 4 hours at a vacuum degree of -0.08 MPa and 40° C., 54 to 82 parts of ethanol, 4 to 8 parts of sodium molybdate vanadate, and 13 to 21 parts of 650 polyamide resin curing agent are added and mixed evenly to obtain a modified epoxy resin coating material; (2) placing 58 to 96 parts of aluminum alloy and 0.2 to 0.4 parts of titanium powder in a furnace, melting at 740 to 780° C. for 40 to 50 minutes, and then casting, wherein the casting temperature is 680 to 720° C., the casting speed is 55 to 75 mm / min, the casting cooling water temperature is 18 to 24° C., and the casting cooling water pressure is 0.05 to 0.85 MPa, placing on a hot rolling mill at 300 to 400° C. to a thickness of 2 to 3 mm, immersing in a water pool at 20 to 30° C. for 5 to 15 seconds, and then standing at 170 to 190° C. for 4 to 12 hours and at 20 to 25° C. for 18 to 36 hours to obtain an aluminum alloy blank; (3) The surface of the aluminum alloy blank is sandblasted, and a modified epoxy resin coating material is applied to the surface of the aluminum alloy blank with a coater, and the coating material is cured at 60 to 70° C. for 8 to 12 hours to obtain a high temperature resistant deformation aluminum alloy.

4. The method for preparing a high temperature resistant deformable aluminum alloy according to claim 3, characterized in that: The epoxy resin model in step (1) is any one of EPM-420, MF-3285, and 3101G.

5. The method for preparing a high temperature resistant deformable aluminum alloy according to claim 3, characterized in that: The preparation steps of the carboxyethylsilanetriol ethanol solution in step (1) are as follows: dissolving 3 to 5 parts of carboxyethylsilanetriol sodium salt in 24 to 40 parts of ethanol, stirring evenly, adding hydrochloric acid ethanol solution to adjust the pH, filtering and collecting the filtrate to obtain the carboxyethylsilanetriol ethanol solution.

6. The method for preparing a high temperature resistant deformable aluminum alloy according to claim 4, characterized in that: The concentration of hydrochloric acid in the hydrochloric acid-ethanol solution is 1 mol / L; the pH value of the solution after pH adjustment is 4-6.

7. The method for preparing a high temperature resistant deformable aluminum alloy according to claim 3, characterized in that: The preparation method of sodium molybdovanadate in step (1) is as follows: 15 to 25 parts of sodium molybdate, 18 to 30 parts of sodium orthovanadate and 132 to 220 parts of water are mixed evenly, transferred into an autoclave, reacted at 200 to 240° C. for 12 to 24 hours, naturally cooled to room temperature, filtered to obtain a solid, washed three times with deionized water and ethanol alternately, dried in an oven at 50 to 60° C. for 10 to 16 hours, and crushed into powder to obtain sodium molybdovanadate.

8. The method for preparing a high temperature resistant deformable aluminum alloy according to claim 3, characterized in that: The aluminum alloy model in step (2) is any one of 6061 and 6063.

9. The method for preparing a high temperature resistant deformable aluminum alloy according to claim 3, characterized in that: The diameter of the rolling rollers in the hot rolling mill in step (2) is 300 to 400 mm.

10. The method for preparing a high temperature resistant deformable aluminum alloy according to claim 3, characterized in that: The thickness of the coating in step (3) is 100 to 120 μm.